THE INFLUENCE OF BUSINESS STRATEGY AND ORGANIZATIONAL CULTURE ON MANAGEMENT ACCOUNTING INFORMATION SYSTEMS - Marlina, Ressy; Hertati, Lesi; Putri, Andini Utari (Transpublika Publisher, 2023)
This study aims to determine the effect of Business Strategy and Organizational Culture on Management Accounting Information Systems for Employees of CV. Srijaya City of Palembang. The selected sample is 40 respondents. The research data was obtained from a questionnaire (primary data). The analysis technique used is multiple linear regression method. The results of data analysis with the help of SPSS 26 showed that the results of the partial hypothesis test (t-test) on business strategy have no significant effect on the management accounting information system. Meanwhile, organizational culture has a significant effect on management accounting information systems. Likewise, the results of the simultaneous test (f-test) based on the coefficient of termination proves that the variables of business strategy and organizational culture simultaneously have a positive and significant effect on the management accounting information system.